Pharmacological Activation Of Aldehyde Dehydrogenase 2 Protects Against Heatstroke-Induced Acute Lung Injury by Modulating Oxidative Stress and Endothelial Dysfunction - Tsai, Hsiao-Ya; Hsu, Yu-Juei; Lu, Cheng-Yo; Tsai, Min-Chien; Hung, Wan-Chu; Chen, Po-Chuan; Wang, Jen-Chun; Hsu, Lung-An; Yeh, Yung-Hsin; Chu, Pauling; Tsai, Shih-Hung (Frontiers in Immunology, 2021)
Heatstroke (HS) can cause acute lung injury (ALI). Heat stress induces inflammation and apoptosis via reactive oxygen species (ROS) and endogenous reactive aldehydes. Endothelial dysfunction also plays a crucial role in HS-induced ALI. Aldehyde dehydrogenase 2 (ALDH2) is a mitochondrial enzyme that detoxifies aldehydes such as 4-hydroxy-2-nonenal (4-HNE) protein adducts. A single point mutation in ALDH2 at E487K (ALDH2*2) intrinsically lowers the activity of ALDH2. Alda-1, an ALDH2 activator, attenuates the formation of 4-HNE protein adducts and ROS in several disease models. We hypothesized that ALDH2 can protect against heat stress-induced vascular inflammation and the accumulation of ROS and toxic aldehydes. Homozygous ALDH2*2 knock-in (KI) mice on a C57BL/6J background and C57BL/6J mice were used for the animal experiments. Human umbilical vein endothelial cells (HUVECs) were used for the in vitro experiment. The mice were directly subjected to whole-body heating (WBH, 42 °C) for 1 h at 80% relative humidity. Alda-1 (16 mg/kg) was administered intraperitoneally prior to WBH. The severity of ALI was assessed by analyzing the protein levels and cell counts in the bronchoalveolar lavage fluid, the wet/dry ratio and histology. ALDH2*2 KI mice were susceptible to HS-induced ALI in vivo. Silencing ALDH2 induced 4-HNE and ROS accumulation in HUVECs subjected to heat stress. Alda-1 attenuated the heat stress-induced activation of inflammatory pathways, senescence and apoptosis in HUVECs. The lung homogenates of mice pretreated with Alda-1 exhibited significantly elevated ALDH2 activity and decreased ROS accumulation after WBH. Alda-1 significantly decreased the WBH-induced accumulation of 4-HNE and p65 and p38 activation. Here, we demonstrated the crucial roles of ALDH2 in protecting against heat stress-induced ROS production and vascular inflammation and preserving the viability of ECs. The activation of ALDH2 by Alda-1 attenuates WBH-induced ALI in vivo.